1989
DOI: 10.1002/jbmr.5650040207
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone 5′-deiodinase activity, nuclear binding, and effects on mitogenesis in umr-106 osteoblastic osteosarcoma cells

Abstract: The hyperthyroid state in vivo is associated with an increase in osteoblast number and activity, suggesting that thyroid hormone may stimulate osteoblast replication and function. We therefore examined the effects of T3 (16-1170 pM) on replication rate as assessed by cell counts in UMR-106 osteoblastic osteosarcoma cells cultured for 5-10 days in medium supplemented with 10% hormone-stripped fetal calf serum (FCS). Despite the virtual absence of thyroid hormone in the control medium (total T3 concentration, 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 44 publications
2
11
0
4
Order By: Relevance
“…This phenotype is consistent with restricted expression Dio2 in osteoblasts and its absence from osteoclasts (19). D1/D2KO mice exhibited a phenotype comparable with D2KO mice, reflecting the absence of D1 activity in bone (16)(17)(18)(19). Thus, reduced toughness and resistance to fracture in D2KO and D1/D2KO mice reveals an important role for D2 in osteoblasts in the optimization of bone strength.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This phenotype is consistent with restricted expression Dio2 in osteoblasts and its absence from osteoclasts (19). D1/D2KO mice exhibited a phenotype comparable with D2KO mice, reflecting the absence of D1 activity in bone (16)(17)(18)(19). Thus, reduced toughness and resistance to fracture in D2KO and D1/D2KO mice reveals an important role for D2 in osteoblasts in the optimization of bone strength.…”
Section: Discussionsupporting
confidence: 71%
“…A minor and transient impairment of weight gain was reported in male D2KO mice, whereas weight gain and growth were normal in D1KO and D1-deficient C3H/HeJ mice and in C3H/HeJ D2KO mutants with D1 and D2 deficiency (11-15). We and others have shown that D1 is not expressed in skeletal cells (16)(17)(18)(19), indicating D1 does not influence T3 action in bone directly. D2 activity has been demonstrated in the embryonic growth plate where it is regulated by the skeletal morphogen Hedgehog (20).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Weight gain and growth, however, were normal in D1KO-and in DIO1-deficient C3H/HeJ mice and in combined C3H/HeJ D2KO mutants with DIO1 and DIO2 deficiency (Berry et al 1993, Schoenmakers et al 1993, Schneider et al 2006, Christoffolete et al 2007). We and others showed that DIO1 is not expressed in bone and cartilage (LeBron et al 1989, Dreher et al 1998, Gouveia et al 2005, Williams et al 2008, indicating that DIO1 does not directly influence T 3 action in bone.…”
Section: Role Of Dio2 In the Skeletonmentioning
confidence: 75%
“…(21) D2 is essential for the local production of T 3 through deiodination of triiodothyroxine (T 4 ). Although earlier studies on the role and functional expression of iodothyronine deiodinase enzymes in the skeleton have been equivocal, (12,14,(22)(23)(24)(25) a recent study reported normal growth in mice with deficiencies in D1 and D2, indicating that D2 may not be critical in skeletal development. (26) This notion was supported in a recent study that demonstrated that D2 activity is restricted to mature osteoblasts, suggesting a possible role for D2 in mature osteoblast function.…”
Section: Introductionmentioning
confidence: 97%